2018
DOI: 10.1002/pfi.21805
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Organizational Citizenship Behavior: A Study of Workplace Spirituality and Employee Retention in Indian Industries

Abstract: The issue of increasing retention and reducing turnover is of paramount importance in organizational life. Workplace spirituality may act as a potential solution for employee attraction and retention mechanisms. To investigate this question, the researchers collected data from 761 executives working with various public‐ and private‐sector industries across India. The findings of the study show a positive association between workplace spirituality and employee retention, whereas partial mediation was observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…The capability of workplace spirituality as a mediator of work engagement might lie in its relationship to meaningful work. Jena and Pradhan ( 2018 ) found that workplace spirituality uniquely impacted the loyalty and commitment of the employees, and they feel more effectively attached to their organization. Furthermore, it will reinforce their devotion to work, giving them a strong sense of contentment (Izak, 2012 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The capability of workplace spirituality as a mediator of work engagement might lie in its relationship to meaningful work. Jena and Pradhan ( 2018 ) found that workplace spirituality uniquely impacted the loyalty and commitment of the employees, and they feel more effectively attached to their organization. Furthermore, it will reinforce their devotion to work, giving them a strong sense of contentment (Izak, 2012 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Dalam konteks organisasi, spiritualitas kerja dianggap sebagai faktor yang sangat potensial bagi organisasi khususnya dalam hal mempertahankan karyawan (Jena & Pradhan, 2018). Spiritualitas kerja juga dipandang sebagai lingkungan yang memfasilitasi karyawan sehingga karyawan merasa lebih termotivasi dalam memanfaatkan potensi yang dimiliki melalui kreativitas, emosi dan kecerdasan (Byrd, 2014).…”
Section: Aunclassified
“…There is strong empirical support to show workplace spirituality as one of the most important antecedents for work engagement. A study by Jena and Pradhan (2018) looked at the dynamics of workplace spirituality in India's public and private sector businesses, and concluded that both developed equally as long as they were associated with employees, resulting in a strong emotional connection and a sense of belonging. According to the study, appropriate intervention mechanisms for instrumentalizing personal roles and organisational goal fit would result in a more engaged and committed workforce.…”
Section: Workplace Spirituality and Work Engagementmentioning
confidence: 99%